Assertividade e autocontrole: interpretação analítico-comportamental - MARCHEZINI-CUNHA, Vívian (2011)
Issues related to assertiveness have been investigated by behavior therapists for over three decades. It is more recent, however, the effort made by behavior-analytic therapists to examine such issues with the same conceptual and methodological tools employed by their colleagues in basic and conceptual research. This study aims to provide a behavior-analytic interpretation of assertive, aggressive and passive behavior patterns. We recovered some definitions of assertiveness/aggressiveness/passiveness and then examined the corresponding phenomena as behavioral relations, discussed some aspects of the behavior-analytic approach of self-control, and suggested that behavioral relations defined as assertiveness/aggressiveness/passiveness may be interpreted as instances of self-control or impulsiveness. Such approach may give rise to new directions in clinical research of social skills from a behavior-analytic standpoint.